Zinc-doped copper oxide nanocomposites reverse temozolomide resistance in glioblastoma by inhibiting AKT and ERK1/2. (27th June 2018) - Wu, Ning; Zhang, Chunyun; Wang, Changhui; Song, Lairong; Yao, Weicheng; Gedanken, Aharon; Lin, Xiukun; Shi, Dayong
Aim: To assess the effect of zinc-doped copper oxide nanocomposites (nZn-CuO NPs) on glioblastoma therapy.Materials & methods: nZn-CuO NPs were synthesized by sonochemical method and its antitumor effects and underlying molecular mechanisms were investigated both in vitro and in vivo .Results: After nZn-CuO NPs treatment, cell proliferation was significantly inhibited in dividing cancer cells but less toxicity was observed in normal cells. In vivo studies show that nZn-CuO NPs inhibited tumor growth in a dose-dependent manner. Further study found that nZn-CuO NPs trigger cell reactive oxygen species (ROS) generation and intrinsic apoptotic pathway. In temozolomide resistance glioblastoma, nZn-CuO NPs disturb cell growth and sphere formation by inhibiting AKT and ERK1/2 activation.Conclusion: nZn-CuO NPs possess the potential to be developed as a novel anti-tumor agent, especially to treat temozolomide resistance glioblastoma.